A miniaturized magnetoelectric composite based on surface-crystallized FeSiB and PMN-PT single crystal - Ziyang Xu; Yicai Ji; Xiamin Huang; Wenjun Shuai; Juan Han; Yu Sun; Xin Zhuang (AIP Advances)
Magnetoelectric composites, consisting of piezoelectric and magnetostrictive materials, are often excited at the acoustic resonance to generate the low frequency signals for communicating in the high-loss media (i.e., underwater/underground channels). The miniaturization of such an antenna is required for many applications, whereas the efficiency is often decreased with the decrease in antenna size. In this work, we fabricate a magnetoelectric composite using a (011)-cut manganese doped Pb(Mg1/3Nb2/3)O3–PbTiO3 single crystal with a quality factor (Qp) of 735 and surface-crystallized FeSiB ribbons. The achieved conversion efficiency is 93.5%. The high resonant frequency (close to 70 kHz) of the device with reduced size increases the magnetic interactions from interlayers, resulting in a lower magnetomechanical coupling coefficient (km) even though the ribbons with tailored domain size are used. Our results indicate that, to date, the primary limiting factors for conversion efficiency during device miniaturization are km and quality factor (Qm) measured from the coil coupled to the magnetostrictive phase of the magnetoelectric composite, rather than the piezoelectric properties.